Respuesta :
For option a,
y - 3x^2 = 3(x^2 + 5) + 1
y = 3x^2 + 3x^2 + 15 + 1
y = 6x^2 + 16
Option a is a quadratic function.
y - 3x^2 = 3(x^2 + 5) + 1
y = 3x^2 + 3x^2 + 15 + 1
y = 6x^2 + 16
Option a is a quadratic function.
Answer:
option:A
Step-by-step explanation:
A quadratic equation is a equation of the type [tex]y=f(x)=ax^{2} +bx+c[/tex]
(a) [tex]y-3x^{2} =3(x^{2}+5)+1\\\\y=3x^2+3(x^2+5)+1\\\\y=3x^2+3x^2+15+1\\\\y=6x^2+16[/tex]
Here on comparing the equation with [tex]y=f(x)=ax^{2} +bx+c[/tex] we have a=6,b=0 and c=16
hence, option A is correct.